Collapsing Glomerulopathy: A Review by the Collapsing Brazilian Consortium - Cutrim, Érico Murilo Monteiro; Neves, Precil Diego Miranda de Meneses; Campos, Marcos Adriano Garcia; Wanderley, Davi Campos; Teixeira-Júnior, Antonio Augusto Lima; Muniz, Monique Pereira Rêgo; Ladchumananandasivam, Francisco Rasiah; Gomes, Orlando Vieira; Vasco, Rafael Fernandes Vanderlei; Brito, Dyego José de Araújo; Lages, Joyce Santos; Salgado-Filho, Natalino; et al. (Frontiers in Medicine, 2022)
Collapsing glomerulopathy (CG) is a clinicopathologic entity characterized by segmentar or global collapse of the glomerulus and hypertrophy and hyperplasia of podocytes. The Columbia classification of 2004 classified CG as a histological subtype of focal segmental glomerulosclerosis (FSGS). A growing number of studies have demonstrated a high prevalence of CG in many countries, especially among populations with a higher proportion of people with African descent. The present study is a narrative review of articles extracted from PubMed, Medline, and Scielo databases from September 1st, 2020 to December 31st, 2021. We have focused on populational studies (specially cross-sectional and cohort articles). CG is defined as a podocytopathy with a distinct pathogenesis characterized by strong podocyte proliferative activity. The most significant risk factors for CG include APOL1 gene mutations and infections with human immunodeficiency virus and severe acute respiratory syndrome coronavirus 2. CG typically presents with more severe symptoms and greater renal damage. The prognosis is notably worse than that of other FSGS subtypes.